Heartmate II outflow graft ligation and driveline excision without pump removal for left ventricular recovery - Khvilivitzky, Katherine (Baylor Health Care System, 2012)
We report interruption of left ventricular assist device (VAD) support by way of outflow graft ligation and driveline excision while leaving the pump in situ. In this case, the indication for mechanical assist device separation was myocardial recovery, which occurred following 9 months of support. This case report demonstrates the feasibility of separating a patient from a VAD without the need for a major reoperative intervention.